Kinetic Characterization and Inhibitor Screening of Pyruvate Kinase I From Babesia microti - An, Xiaomeng; Yu, Long; Wang, Sen; Ao, Yangsiqi; Zhan, Xueyan; Liu, Qin; Zhao, Yangnan; Li, Muxiao; Shu, Xiang; Li, Fangjie; He, Lan; Zhao, Junlong (Frontiers in Microbiology, 2021)
The apicomplexan Babesia microti is a main pathogenic parasite causing human babesiosis, which is one of the most widely distributed tick-borne diseases in humans. Pyruvate kinase (PYK) plays a central metabolic regulatory role in most living organisms and catalyzes the essentially irreversible step in glycolysis that converts phosphoenolpyruvate (PEP) to pyruvate. Hence, PYK is recognized as an attractive therapeutic target in cancer and human pathogens such as apicomplexans. In this study, we cloned, expressed, and purified B. microti PYK I (BmPYKI). Western blotting illustrated that anti-rBmPYKI antibody could specifically recognize the native BmPYKI protein in the lysate of B. microti with a 54-kDa band, which is consistent with the predicted size. In addition, the enzymatic activity of the purified recombinant PYKI (rPYKI) was tested under a range of pH values. The results showed that the maximum catalytic activity could be achieved at pH 7.0. The saturation curves for substrates demonstrated that the Km value for PEP was 0.655 ± 0.117 mM and that for ADP was 0.388 ± 0.087 mM. We further investigated the effect of 13 compounds on rBmPYKI. Kinetic analysis indicated that six inhibitors (tannic acid, shikonin, apigenin, PKM2 inhibitor, rosiglitazone, and pioglitazone) could significantly inhibit the catalytic activity of PYKI, among which tannic acid is the most efficient inhibitor with an IC50 value 0.49 μM. Besides, four inhibitors (tannic acid, apigenin, shikonin, and PKM2 inhibitor) could significantly decrease the growth of in vitro-cultured B. microti with IC50 values of 0.77, 2.10, 1.73, and 1.15 μM. Overall, the present study provides a theoretical basis for the design and development of new anti-Babesia drugs.